RESPON JARAK TANAM JAJAR LEGOWO DAN JUMLAH BIBIT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI SAWAH (Oryza sativa L.) (STUDI KASUS DI KECAMATAN KAUBUN KABUPATEN KUTAI TIMUR) - Rohaeni, Nani (Jurnal Magrobis, 2017)
The research aims to: 1. Determined response of pair rows spacingusage and number of seeds per hole that effect on growth and yield of lowland rice (Oryza sativa L.). 2. Obtained the proper pair rows spacingand number of seeds per hole, so that it can provide the best results on growth of lowland rice (Oryza sativa L.)The reserach was conducted on May up to August 2016, reserach located on Bumi Rapak Village, District of Kaubun, East Kutai Regency. Research design used a Randomized Block Design (RBD) with experimental factorial 3x2and each treatment has 4 replicated which is consists of 2 factors, there are 24 research plots with each replicate contained 10 plant samples. First factor; (G1), pair rows spacing2:1 (G2), pair rows spacing4:1 (G3) pair rows spacing6:1. Second factor; number of seeds, 1 stem per planting hole ( B1), number of seeds, 2 stems per planting hole (B2). Analysis data using ANOVA tables with advanced test Least Significant Difference (LSD) level 5%.The research results showed that treatment of pair rows spacing and number of seeds per hole showed non significant effect on plant height, total of tiller, productive tiller, total of grain, and percentage of filled grain. On potential results showed non significant effect with the acquisition of grain 4.329 (t/ha) on treatment interaction of pair rows spacing4:1 and number of seed, one per hole.Keywords: Lowland Rice, Pair Rows (jajar legowo), Number of Seed